Abschlussbericht für das Projekt LightWave - Pflaum, Christoph; Hertel, Kai (2012)
UnivIS-Import:2016-06-30:Pub.2012.tech.IMMD.c3sim.abschl

Analysis of Optical Nanostructures of Thin-Film Solar Cells Using High Performance Simulations - Jandl, Christine Angelika; Hertel, Kai; Pflaum, Christoph; Stiebig, HElmut (Optical Nanostructures for Photovoltaics, 2010)
Short-circuit current density and the quantum efficiency of thin-film solar cells are calculated by simulating Maxwell's equations to improve light-management in these solar cells. Complete solar cell structures, based on AFM-scans, are simulated with high performance computing. © OSA/PV 2010.
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.lsinfs.analys

An image processing approach to approximating interface textures of microcrystalline silicon layers grown on existing aluminum-doped zinc oxide textures - Hertel, Kai; Hüpkes, Jürgen; Pflaum, Christoph (Optics Express, 2013)
We present an algorithm for generating a surface approximation of microcrystalline silicon (mc-Si) layers after plasma enhanced chemical vapor deposition (PECVD) onto surface textured substrates, where data of the textured substrate surface are available as input.We utilize mathematical image processing tools and combine them with an ellipsoid generator approach. The presented algorithm has been tuned for use in thin-film silicon solar cell applications, where textured surfaces are used to improve light trapping. We demonstrate the feasibility of this method by means of optical simulations of generated surface textures, comparing them to simulations of measured atomic force microscopy (AFM) scan data of both Aluminum-doped zinc oxide (AZO, a transparent and conductive material) and mc-Si layers. © 2013 Optical Society of America.
UnivIS-Import:2015-03-09:Pub.2013.tech.IMMD.lsinfs.animag

High Performance Computing for the Simulation of Thin-Film Solar Cells - Jandl, Christine Angelika; Hertel, Kai; Dewald, W; Pflaum, Christoph (High Performance Computing in Science and Engineering Garching/Munich 2009, 2010)
UnivIS-Import:2015-04-16:Pub.2010.tech.IMMD.c3sim.highpe

Simulation of optical Waves in thin-film Solar Cells - Pflaum, Christoph; Jandl, Christine Angelika; Hertel, Kai; Rahimi, Zhabiz (Innovatives Supercomputing in Deutschland : inSiDE, 2010)
In order to increase the efficiency of thin-film solar cells, the nanostructure of these cells has to be optimized. To this end, simulations of the optical wave in thin-film solar cells are required. The frequency dependence of the refraction index of materials, like amorphous silicon (a-Si:H), cannot be described by dispersive models like Drude model. Therefore, single frequency simulations for the whole solar spectrum have to be performed. To discretize materials with negative permittivity efficiently, we developed a new finite-difference-frequencydomain method to avoid computationally intensive simulations. To demonstrate the efficiency of our method, we present 3-dimensional simulations for a tandem solar cell including interfaces described by AFM-scans. Plasmonic effects at the silver back-contact show the efficiency of our discretization in case of materials with negative permittivity. ©2010 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.IMMD.lsinfs.simula_2

Simulation of silicon thin-film solar cells for oblique incident waves - Jandl, Christine Angelika; Hertel, Kai; Pflaum, Christoph; Stiebig, HElmut (Proceedings of SPIE, 2011)
To optimize the quantum efficiency (QE) and short-circuit current density (JSC) of silicon thin-film solar cells, one has to study the behavior of sunlight in these solar cells. Simulations are an adequate and economic method to analyze the optical properties of light caused by absorption and reflection. To this end a simulation tool is developed to take several demands into account. These include the analysis of perpendicular and oblique incident waves under E-, H- and circularly polarized light. Furthermore, the topology of the nanotextured interfaces influences the efficiency and therefore also the short-circuit current density. It is well known that a rough transparent conductive oxide (TCO) layer increases the efficiency of solar cells. Therefore, it is indispensable that various roughness profiles at the interfaces of the solar cell layers can be modeled in such a way that atomic force microscope (AFM) scan data can be integrated. Numerical calculations of Maxwell's equations based on the finite integration technique (FIT) and Finite Difference Time Domain (FDTD) method are necessary to incorporate all these requirements. The simulations are performed in parallel on high performance computers (HPC) to meet the large computational requirements. © 2011 Copyright Society of Photo-Optical Instrumentation Engineers (SPIE).
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.c3sim.simula
Keywords: AFM scan; oblique incident waves; thin-film solar cells

Simulation of thin-film silicon solar cells with integrated AFM scans for oblique incident waves - Jandl, Christine Angelika; Hertel, Kai; Pflaum, Christoph; Stiebig, HElmut (Proceedings of 26th European Photovoltaic Solar Energy Conference, 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.c3sim.simula_4